Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1962
DOI: 10.1182/blood.v20.4.393.393
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chromosome Constitution in Chronic Myelocytic Leukemia and Other Myeloproliferative Disorders

Abstract: The frequency of the Ph1 chromosome in freshly aspirated marrow cells of 14 patients with typical chronic myelocytic leukemia processed by a "direct technic" without resort to culture or colchicine was significantly higher (> 75 per cent) than that observed in the cultured blood cells (< 35 per cent) of the same subjects. The karyotypic abnormally of the abbreviated G-group chromosome would appear not to be related to therapy, since the frequency with which it occurred was not materially affected by trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1964
1964
1977
1977

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Finally, there exists the possibility of a relationship between the radiotherapy for the lymphosarcoma and tlie later development of leukemia, hardly a new concept in the pathogenesis of leukemia. Of interest in this rep r d are reports from Englandlg and the United Statess, 15 which stress the high incidence of prior radiotherapy in Phl chromosome negative cases of chronic granulocytic leukemia and, indeed, our case seems to represent another example of this correlation.…”
Section: Cancer June 1966mentioning
confidence: 55%
“…Finally, there exists the possibility of a relationship between the radiotherapy for the lymphosarcoma and tlie later development of leukemia, hardly a new concept in the pathogenesis of leukemia. Of interest in this rep r d are reports from Englandlg and the United Statess, 15 which stress the high incidence of prior radiotherapy in Phl chromosome negative cases of chronic granulocytic leukemia and, indeed, our case seems to represent another example of this correlation.…”
Section: Cancer June 1966mentioning
confidence: 55%
“…(Tjio & Wang 1962). Sandberg et al (1962) did not use any. We found that while there was no appreciable difference between colchicine and colcemid, a high concentration of either yielded fewer mitotic figures as well as overcontracted chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Similar obesrvations have been described for the incidence of the Phl chromosome in C M L before and after therapy. 2 The fuzzy and ill-defined appearance of acute leukemic chromosomes often makes it possible to identify the leukemic metaphases in marrow with great ease. This appearance contrasts with the well-defined cells of the marrow.…”
Section: Discussionmentioning
confidence: 99%